(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to the study of the wedding rites of the Uzbeks of the city of Osh, which were formed at the intersection of cultural interactions. The key stages of the wedding ritual are examined, including matchmaking, the nikah ceremony, festive feasts and post-wedding customs. Particular attention is paid to the analysis of the influence of neighboring peoples, such as the Kyrgyz, Tajiks, Russians and Turks, who made changes to the musical accompaniment, national costumes, wedding dishes and the symbolism of rituals. The historical conditionality of cultural interactions and their role in the formation of modern traditions is emphasized. The article also examines modern trends in the transformation of the wedding ritual under the influence of globalization, urban culture and Western wedding traditions, which are manifested in a reduction in the duration of the holiday, a change of outfits and a simpler format of ceremonies. The importance of preserving cultural heritage in the face of modern challenges is emphasized, especially in the context of rapid cultural exchange and globalization, which require adaptation of traditions.